Effect of Plate Materials and Operational Parameters on Hybrid Phsyco-Biological Units for Palm Oil Mill Effluent - Daffa Aqilla Prayogi; Yudi Chadirin; Yanuar Chandra Wirasembada; Allen Kurniawan (Jurnal Teknik Sipil dan Lingkungan, 2026)
Indonesia’s palm oil industry generates large volumes of palm oil mill effluent (POME) characterized by high organic load and suspended solids, requiring effective treatment. This study evaluates a continuous hybrid system consisting of a kapok fiber(KF) pre-treatment unit, electrocoagulation (EC) reactor, and Moving Bed Biofilm Reactor (MBBR), operated under varying plate materials (Fe, Al, Cu) at 24 V and 10 A. The system treated raw POME (pH 3.4; sCOD 20,796 mg/L; TSS 25,610 mg/L; oil and grease 3,243mg/L) over 10-day operational cycles per condition. Results show that copper electrodes achieved the highest performance, with sCOD removal up to 66% and oil and grease removal up to 81.38%, alongside improved TSS reduction. The KF unit contributed 46–53% oil and grease removal, while EC primarily reduced suspended solids and adjusted pH, supporting stable MBBR performance. The combined configuration highlights the interaction between physicochemical and biological processes, where electrode selectionand pre-treatment significantly influence overall system efficiency. These findings provide insight into optimizing integrated treatment strategies for high-strength POME, although additional polishing steps are still required to meet discharge standards.